Atividade secretória e histologia uterina de cadelas pré-púberes com ablação parcial do desenvolvimento das glândulas endometriais - Martins, Bianca Barcelos (2013)
The use of steroids with actions in the female reproductive system may affect the development and differentiation of the uterus, which can lead to abnormal development of endometrial glands, with decreased reproductive efficiency and even sterility. Thus, this methodology could be applied in the population control of dogs. However, in cases of partial inhibition of the development of the glands is not known effects of steroids on the functionality formed glands, as well as the possible occurrence of endometrial fibrosis. This study aimed to evaluate the secretory activity of the endometrial glands of prepubertal bitches undergoing a protocol for partial ablation of endometrial glands development. We used sixteen female mongrel bitches from different litters, distributed in the MPA group (n = 8), females that received injections of medroxyprogesterone acetate (10mg/kg/SC), every 3 weeks, from day 1 after birth until the age of six months, and C (n = 8), control females, untreated, which received applications of 0.9% NaCl solution. At 6 months of age, ovariohysterectomy was performed in all animals, and samples of uterine horns were collected and fixed for histology and histochemistry. To evaluate the intensity of uterine secretion (grades 1-4), the stains of periodic acid Schiff (PAS) and Alcian Blue (AB) pH 2.5 were used. For histological analysis we used Masson s trichrome and toluidine blue staining. Statistical analysis was performed by Kruskal-Wallis test, using the R software, with significance level of 5%. No dog in both groups exhibited cystic endometrial hyperplasia (HCE) and presence of content in the uterine lumen. For PAS only the grades 1 (absent) and 2 (mild) were observed in both groups, without difference between groups. However, the MPA showed greater intensity of uterine secretion (grade 2) in comparison to the C group (p <0.05). With respect to AB pH 2.5, in both groups we also found only the grades 1 (absent) and 2 (mild), without statistical difference between groups. There was no Masson s trichrome staining in the periglandular region in both groups. There was greater amount of mast cells present in the region of the myometrium in relation to the endometrium in both groups. It is concluded that prepubertal bitches with partial ablation of uterine adenogenesis present minimal uterine secretory activity, absence of uterine periglandular fibrosis and presence of larger amount of mast cells in the myometrium in relation to the endometrium